2022
DOI: 10.55593/ej.26102a4
|View full text |Cite
|
Sign up to set email alerts
|

L2 Learners’ Understanding of Achievement Emotions and Emotion Regulation Strategies: Contributions of a Longitudinal Emotion Regulation Initiative

Abstract: Developing L2 learners’ emotional balance through adaptive regulation is a significant determinant of successful learning. Despite the recent surge of interest in emotion regulation (ER) programs, research on L2 learners’ ER strategies is surprisingly underdeveloped. To address this gap, the current qualitative study explored ten L2 learners’ understanding of achievement emotions and ER strategies throughout a longitudinal ER-oriented training course. Data were collected from four rounds of semi-structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The multifunctional benefits of ERSs in the language learning context (MacIntyre et al, 2019;Yu et al, 2022) seem to be possible and reasonable. Moreover, previous studies on the instruction of ERSs have demonstrated their impact on learners' well-being, increasing learning opportunities related to their achievements, better teacher-student relationships, and developing learners' emotional balance (Karimi et al, 2022;Oxford, 2016;Webb et al, 2012). In all, speaking of the ERSs' significance, the studies highlight the necessity of considering low achievers' achievement emotions in their struggle with affective, metacognitive, and social strategies (Jun-ming, 2017), and maximizing enjoyment in the learning process (Zheng & Zhou, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifunctional benefits of ERSs in the language learning context (MacIntyre et al, 2019;Yu et al, 2022) seem to be possible and reasonable. Moreover, previous studies on the instruction of ERSs have demonstrated their impact on learners' well-being, increasing learning opportunities related to their achievements, better teacher-student relationships, and developing learners' emotional balance (Karimi et al, 2022;Oxford, 2016;Webb et al, 2012). In all, speaking of the ERSs' significance, the studies highlight the necessity of considering low achievers' achievement emotions in their struggle with affective, metacognitive, and social strategies (Jun-ming, 2017), and maximizing enjoyment in the learning process (Zheng & Zhou, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the current landscape of research on emotions in second language learning primarily examines individual emotions in isolation, often without fully appreciating their intricate interconnectedness (Helgesen, 2016;Jin & Zhang, 2018). Insight into the analysis of achievement emotions and their regulation remains relatively limited (Bielak & Mystkowska-Wiertelak, 2020;Karimi et al, 2022). Bielak and Mystkowska-Wiertelak (2020) underscore the necessity of achieving equilibrium among achievement emotions through effective emotion regulation.…”
mentioning
confidence: 99%
“…Recent studies on the contributions of emotions and positive psychology to SLA have highlighted the significance of EFL learners' emotional balance and the protective role of adaptive ER strategies in strengthening students' well-being as well as promoting successful learning outcomes (Bielak & Mystkowska-Wiertelak, 2020;Karimi et al, 2022;MacIntyre et al, 2019;Oxford, 2017). Despite a wealth of emotion research conducted in Iran in recent years, it seems that the agenda for adaptation and validation of a multicomponential context-specific ER scale has not entered the field of language learning.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the plethora of research conducted on EFL learners' emotions (e.g., Dewaele et al, 2019;Jin & Zhang, 2018;Shao et al, 2019), and self-regulation strategies (e.g., Oxford, 2017;Zimmerman, 2008), scant attention has been devoted to the regulation of emotions (Greenier et al, 2021;Karimi et al, 2022). Due to the paucity of research focusing on ER in the ESL/EFL context, further investigations are required to fill the existing gap (Bielak & Mystkowska-Wiertelak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, achievement emotions significantly influence intrinsic and extrinsic motivation (Pekrun, 1992). Due to this importance, several studies have examined the influence of achievement emotions in relation to learning in the classroom (Behrens et al, 2019;El-Dakhs et al, 2022;Stephan et al, 2019), studying (Karimi et al, 2022;Pekrun et al, 2011;Peterson et al, 2015) and taking exams (Daniels & Gierl, 2017;Dermitzaki et al, 2016;Harley et al, 2020). These studies, however, have rarely compared students' achievement emotions in computer-based versus paper-based exams.…”
Section: Introductionmentioning
confidence: 99%